The Effect of Using Rhythmic Gymnastics Videos and Traditional Games on Youtube Applications on Gross Motor Development in Early Childhood - Adolfiron Luji; Irma Yuliantina (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
Early childhood education covers a lot of ground, and one of the topics is gross motor skills, which involves teaching children how to move the largest and smallest muscles of their bodies, hands, and feet in an effort to help them children whose muscles are not yet strong. The method used in this research is a quantitative research method with a quasi-experimental type used by researchers in conducting research on East Oesapa Nazareth Preschool children. The results showed that there was a significant difference between the pre-test and post-test scores in the control and experimental groups. In the control group, the mean score increased from 30.00 in the pre-test to 31.80 in the post-test, with a statistically significant difference (p 0.002). In the experimental group, there was a greater increase from 30.60 in the pre-test to 37.10 in the post-test, with the difference also being significant (p 0.037). This shows that the use of rhythmic exercise videos and traditional games has a greater impact on the gross motor development of young children. The previous explanation shows that there are significant differences and influences between children who use rhythmic exercise videos and traditional games on the YouTube application. Both the pretest and posttest showed significant results and there was an influence before and after the treatment was given. One thing we can take from this research is that young children, especially those can benefit greatly from watching rhythmic exercise videos on YouTube and traditional games to improve their motor skills.